Reconstructing South Asia - Raju, Adluri Subramanyam (ed.) (New Delhi, 2007)
A collection of articles by the scholars across the South Asian region, attempts to suggest ways and means to overcome the problems of varied colours-major bottlenecks in achieving a particular identity in affirmation-to reconstruct South Asia region. The need of a South Asian Union and a single currency in the region and other issues like peace, security, economic, cultural and political issues are well discussed from the people centric perspective.
Keywords: Economic development